Tensile and Deformation Behavior of Auxetic Plied Yarns. Issue 12 (4th August 2017) - Ng, Wing Sum; Hu, Hong
Abstract : This paper presents an experimental study of tensile and deformation behavior of an auxetic plied yarn structure. The basic configuration of the plied structure formed with two soft yarns and two stiff yarns was firstly introduced. Based on this 4‐ply helix structure, six kinds of yarn samples were made by different combinations of soft yarns, stiff yarns and twist levels. These yarn samples were first tested and the effects of different design parameters were analyzed. Apart from the tensile test, changes in the internal structure of two samples upon stretching were also studied through microscopic examination. Finally, double helix yarn and 6‐ply auxetic yarn were made for a comparative purpose to investigate the effect of helical structure. The study shows that all of the 4‐ply auxetic yarn samples exhibit negative Poisson's ratio (NPR) throughout the entire tensile process, and the magnitude of NPR gets larger with a smaller soft yarn diameter, a higher tensile modulus of stiff yarn and a lower twist level. The study also shows that auxetic behavior inside the 4‐ply structure is generated by the interplay between the soft yarns and stiff yarns and 4‐ply auxetic yarns have the advantages to produce immediate auxetic effect upon stretching. Abstract : How does the auxetic plied yarn produce negative Poisson's ratio? In this paper, tensile properties and auxetic behavior of the 4‐ply auxetic yarns are characterized with a combination of longitudinal and cross‐sectional methodologies. In addition, a new kind of auxetic plied yarn in a 6‐ply structure is proposed and investigated. A schematic diagram of the two kinds of auxetic plied yarns and their respective cross‐section at different states is presented here.